Biogenesis of cellular iron-sulfur proteins: the essential role of mitochondria and the CIA machinery - Lill, Roland (Henry Stewart Talks, 2018)
Cytosolic and nuclear Fe/S proteins maturation, Role of mitochondria in cytosolic and nuclear Fe/S protein biogenesis, Functions of proteins involved in Fe/S protein biogenesis, Importance of Fe/S protein biogenesis for genome maintenance